Reforms in Medical Education: Trends and Challenges - Anwar, AKM Nurul (Journal of Chittagong Medical College Teachers’ Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7660 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):1-2